Հայոց ցեղասպանութեան նուիրուած սուրիական ֆիլմաշարի, թատերգութեան եւ վաւերագրական ժապաւէնի երգ-երաժշտութիւններ - Գաթրճեան, Աւօ (Հայաստանի ազգային գրադարան / National Library of Armenia, 2023)
The article refers to clarifying the reality of the Armenian Genocide through Syrian films, series, plays, and documentaries. The author studied in this article music and songs showed by syrians in plays such as Mamduh Adwan’s “Days of hunger”, and series like “Brothers of the land” etc. It is noted that by using song and music, Syrian arabs expressed their emotions and point of view toward the terrible and horrifying act of the Armenian genocide.
Գիտամեթոդական էլեկտրոնային հանդես / Գլխավոր խմբագիր` Աննա Չուլյան ; Պատասխանատու խմբագիր՝ Հայկանուշ Ղազարյան ․- Երևան ։ «Գիրք» հրատարակչություն , 2023 ․- N 2 .- էջ 124-129
Keywords: Գրադարանագիտություն, մատենագիտություն և արխիվավարություն